Islam Moderat dan Islam Konservatif di Youtube - Romario, Romario (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2024)
Generation Z can be categorized as digital natives, they have mastery in the use of technology. Generation Z accesses religious knowledge not only through religious institutions, but also on social media. Research by the Center for the Study of Islam and Society shows that generation Z consumes a lot of religious knowledge through social media, this phenomenon gives rise to a conservative religious model (Merit Indonesia 2021). The occurrence of religious conservatives cannot be separated from the content available and the popularity of Islamic sites or conservative Islamic accounts, both on Instagram and YouTube. The moderate religious organizations NU and Muhammadiyah are not very prominent in the online space, on YouTube Rodja TV, Yufid TV, Salafi-affiliated Ammar TV get more subscribers than TVMU affiliated with Muhammadiyah as well as Aswaja Tube, NU Channel and NUTV which are affiliated with NU.